2012
DOI: 10.1016/s0140-6736(12)61396-8
|View full text |Cite
|
Sign up to set email alerts
|

Apologising for Nazi medicine: a constructive starting point

Abstract: At long last: in May 2012 the German Medical Association (GMA) has apologised for medical atrocities under National Socialism (appendix). Although overdue, the apology is necessary and highly commendable, not least as survivors of medical atrocities and persecution are still living. German medicine between 1933 and 1945 saw a colossal breach of the ethics of patient care: doctors initiated and implemented an estimated 350,000 coerced sterilisations and 260,000 killings of mentally ill and disabled patients, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Recall the very slow drumbeat of history after World War II: the final judgment at the Nuremberg Medical Trials, issued April 1949, 96 the Declaration of Geneva, adopted in 1948 by the newly formed World Medical Association and last revised in 2006, 97 and the Nuremberg Declaration of the German Medical Assembly in 2012. 98 These three documents over a 60 year period demonstrate progress but also the ponderous pace at which the medical community has responded to its own extraordinary transgressions. This saga continues to haunt all health professionals throughout the world.…”
Section: Resultsmentioning
confidence: 99%
“…Recall the very slow drumbeat of history after World War II: the final judgment at the Nuremberg Medical Trials, issued April 1949, 96 the Declaration of Geneva, adopted in 1948 by the newly formed World Medical Association and last revised in 2006, 97 and the Nuremberg Declaration of the German Medical Assembly in 2012. 98 These three documents over a 60 year period demonstrate progress but also the ponderous pace at which the medical community has responded to its own extraordinary transgressions. This saga continues to haunt all health professionals throughout the world.…”
Section: Resultsmentioning
confidence: 99%
“…The horrific experiments perpetrated by Nazi doctors between 1933 and 1945 on concentration camps prisoners are well-known, including surgical and radiation sterilization as well as drug trials, often to test treatments for diseases with which the victims had been deliberately infected [ 19 , 20 ]. While consent was not sought from these victims, a distinction must be drawn between these atrocities, and paternalism.…”
Section: Nazi Experimentationmentioning
confidence: 99%
“…I also sought to bring the findings and conclusions to the attention of colleagues and medical students and to encourage (together with other colleagues) medical institutions and professional organizations to confront their Nazi past (e.g., Kolb et al 2012). I found that the decades of refusal by both individual physicians and medical organizations to confront this past, to acknowledge extreme forms of wrongdoing, and to investigate their origins, were an extreme expression of a broader tendency in the profession not to admit mistakes and not to investigate the genesis and mechanisms of malpractice as described, for example, by David Rothman (2000a).…”
Section: Volker Roelckementioning
confidence: 99%